Effects of process parameters on selected properties of liquid compression-molded vinyl ester sheets - Abd. Rahman, Mohamed; Salit, Mohd. Sapuan; Abdan, Khalina (Universiti Putra Malaysia Press, 2011)
Vinyl esters combine the best of polyesters and epoxies in terms of properties and processing. Without complicating presence of reinforcing fibres, this study investigated the effects of catalyst amount, preheating time, molding temperature, and pressure on flexural and water absorption properties of cast vinyl ester (VE) using a factorial experiment. Longer preheating time enhanced the stiffness of VE, while higher molding pressure reduced the flexural modulus. All the four factors did not affect the flexural strength and elongation at the break of molded VE significantly. Using a high molding pressure also caused molded VE to have higher water absorption for a long water exposure period. Meanwhile, greater water absorption at bigger amount of catalyst and higher preheating temperature indicate possible interactions between these factors. The results suggest possible negative effects of high molding pressure through the increase in the network of micro-cracks, and thus lowering the integrity of cast VE sheets. Judicious selection of the process parameters was required in order to obtain good quality molded VE sheets and by extension fibre-reinforced VE composites. Molded VE-unsaturated polyester (UP) blend is a significantly different material which is 1.49 times stronger, 2.38 times more flexible, but it is 0.69 less stiff than neat VE and with significantly higher water absorption. The results obtained warrant for a further investigation in process optimization of VE molding and the use of VE-UP blend as a matrix for natural fibre-reinforced composites.